Zinc as an inhibitor of NMDA receptor can exhibit antidepressant effect - Novi Dewi Tanjung; Ninik Mudjihartini (World Nutrition Journal, 2023)
Background : New antidepressant strategies are needed, due to unsatisfactory clinical efficacy and many side effects of commonly used drugs. Recent studies linking the pathophysiology of depression with glutamatergic imbalance. There is hyperactivity of the main excitatory system (glutamatergic) to its inhibition (GABAergic). N-methyl D-aspartate (NMDA) receptors as a part of glutamatergic synapses are potential targets for intervention. Antagonist administration for glutamatergic systems, such as zinc, can exhibit antidepressant effects. Objective : To observe the effect of zinc administration on NMDA receptors in depressed subjects Methods : In this paper, we provide a literature review. The method to achieve the objective consists of using literature exploration, which was conducted from February to June 2022 by searching the relevant studies from several databases. Results : Study trials both in human and animal subjects reveal that depression is associated with a lower concentration of zinc. Comparison between the lowest zinc intake with the highest zinc intake had significantly lower incidence of developing depression. Dietary zinc deficiency induces depression along with upregulation of the NMDA receptor complexes. Zinc’s antidepressant effects might be mediated through its action reducing NMDA channel-opening frequency. Conclusions : The presence of zinc may downregulate the glutamate response in binding to NMDA receptors. Because of numerous studies about the connection between zinc and depression, it seems that zinc may have the potency to develop new antidepressants. Since the capability of zinc administration to reduce depressive symptoms, it is expected leading to increased medication adherence, lower costs and better outcomes.